THE ROLE OF PODCASTS TO ENHANCE STUDENT’S LISTENING SKILLS - Musayeva Nozima Esakhanovna (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
Using a podcast as multimedia can be useful as a tool for listening skills. Students and teachers can take podcasts as listening material and use them widely within the subject. Podcast material used for listening comprehension provides students with authentic and contextual material. Podcasts offer an ideal medium for the creative creation of preferred learning by students and provide a fun way for students and teachers to learn listening content or material. Podcasts, in particular, increase students’ interest in listening to the English language, making it easy and convenient to learn the language of the country being studied. The purpose and objectives of this scientific article is to highlight the importance of providing students with podcasts as listening materials to improve students’ listening skills.